The Good Neighbor Policy in a geopolitical context: 1934--1941 - Ruano de la Haza, Jonathan C (University of Ottawa (Canada), 2007)
Since his first term, Franklin D. Roosevelt presented the Good Neighbor Policy as a remedy for past wrongs (such as military intervention) done to Latin America. After 1935, however, Roosevelt used the Good Neighbor Policy to achieve his internationalist goals in the realm of economic and military cooperation. Part I, dealing with economics, shows that the Roosevelt administration began waging economic warfare in Europe, the Far East and the Americas against the revisionist powers as early as 1934 and that the trade offensive in Latin America was part of a wider policy of economic aggression. Part II argues that the Roosevelt administration actively sought Latin America's cooperation in military matters after 1935. As this thesis will show, the Roosevelt administration was interested in Latin America's strategic location because of its close proximity to the West African coast and as producer of strategic raw materials. Therefore, Roosevelt's Good Neighbor Policy sought to establish bases in Latin America to secure supply routes to Africa and to integrate Latin America's primary economy into the U.S. war economy.
Keywords: History, United States.; Political Science, International Law and Relations.